Pengaruh Metode Demonstrasi Terhadap Peningkatan Hasil Belajar Siswa Kelas III SDN 168 Seluma - Midianah, Midianah (GHAITSA : Islamic Education Journal, 2020)
The purpose of this study is expected to be a special reference for developing learning methods that are right for the benefit of students. This research is a classroom action research, which is carried out in stages to get the desired results. This type of research is classroom action with a workflow covering 4 stages. This study uses a student action research design (PTS) which includes qualitative description research, which takes place in an iterative cycle. Each cycle is carried out as described by (Hopkins 1993: 48) which includes planning activities implementing actions, observation and reflection. Based on the results of the analysis of the data that has been described, the following conclusions can be drawn: (1) The use of the demonstration method can improve learning outcomes of natural science subject matter subject matter and its changes through demonstration methods in learning in class III of SD Negeri 168 Seluma 2019 school year / 2020 (2) The action process evaluation activity showed that the average value of students in cycle I was 71 and rose again in cycle II to 78. Students who completed in cycle I were 14 students or 70% and in the improvement cycle to 19 students or 95%.